2004
DOI: 10.1021/la036036x
|View full text |Cite
|
Sign up to set email alerts
|

Water at Hydrophobic Substrates:  Curvature, Pressure, and Temperature Effects

Abstract: We studied the water density profile close to spherical and planar hydrophobic objects using molecular dynamics (MD) simulations. For normal pressure and room temperature, the depletion layer thickness of a planar substrate is approximately 2.5 Angstroms. Even for quite large spherical solutes with a radius of R = 18 Angstroms, the depletion layer thickness is reduced by 30%, which shows that substrate curvature and roughness is an experimentally important factor. Rising temperature leads to a substantial incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
108
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(121 citation statements)
references
References 29 publications
12
108
1
Order By: Relevance
“…In contrast, molecular dynamics computer simulations (22)(23)(24) indicate a depletion region extending at most 2.5 Å from the hydrophobic surface, whereas recent Monte Carlo simulations show that dissolved gases such as N 2 adsorb as a monolayer at the hydrophobic-water interface with a density that is Ϸ30 times higher than in the bulk solution (25). However, no stable bubbles are predicted by these simulations, and they are not expected thermodynamically.…”
mentioning
confidence: 64%
“…In contrast, molecular dynamics computer simulations (22)(23)(24) indicate a depletion region extending at most 2.5 Å from the hydrophobic surface, whereas recent Monte Carlo simulations show that dissolved gases such as N 2 adsorb as a monolayer at the hydrophobic-water interface with a density that is Ϸ30 times higher than in the bulk solution (25). However, no stable bubbles are predicted by these simulations, and they are not expected thermodynamically.…”
mentioning
confidence: 64%
“…Another issue that may be relevant to the charging of small objects or convexities of a surface is the dependency of the adsorbed water density profile and the surface potential on the curvature radius of the object. 95 In regard to these points, it is also reasonable to expect that the shape of the apex of the rubber, being either concave or convex, will have an impact on the charging characteristics, a trend already observed by Shaw. 9 The release of the hydronium ions at the front of the water meniscus during rubbing may also be triggered by self-repulsion of the positive ions due to their own increasing space charge field.…”
Section: Water Dissociation and Ion Separationmentioning
confidence: 76%
“…As the main result of those experiments, it was shown that the effective depletion thickness (defined as the thickness of a step-like depletion layer consisting of vacuum with the same integrated depleted amount as the rounded and smeared-out depletion profiles found in experiments) is roughly 2.5 Angstroms on hydrophobic poly-styrene substrates [273] and 5 Angstroms on hydrophobic self-assembled monolayers [274] using neutron reflectivity methods, and about 1 Angstrom on paraffin substrates using X-ray reflectivity measurements [275]. The reason for the discrepancies among different experiments is not well understood, but since the strength of water depletion is reduced with decreasing radius of curvature of the hydrophobic solutes [276], it is clear that surface roughness is one important factor (among many others, as e.g. small traces of attractive interactions between wall and water molecules) and will, if present, reduce the depleted amount.…”
Section: Water At Hydrophobic Substratesmentioning
confidence: 92%
“…In Figure 28a) a snapshot of the MD simulation is shown, which serves to illustrate the geometry of the system [276]. The alkane molecules form a compact slab in the middle of the simulation box.…”
Section: Water At Hydrophobic Substratesmentioning
confidence: 99%